Are body surface area based estimates of liver volume applicable to children with overweight or obesity? An in vivo validation study - Chelsea Hosey‐Cojocari; Sherwin S. Chan; Chance S. Friesen; Amie Robinson; Veronica Williams; Erica Swanson; Daniel O'Toole; Jansynn Radford; Neil Mardis; Trevor N. Johnson; J. Steven Leeder; Valentina Shakhnovich (Wiley, 2021)
Abstract The liver is the primary organ responsible for clearing most drugs from the body and thus determines systemic drug concentrations over time. Drug clearance by the liver appears to be directly related to organ size. In children, organ size changes as children age and grow. Liver volume has been correlated with body surface area (BSA) in healthy children and adults and has been estimated by functions of BSA. However, these relationships were derived from "typical" populations and it is unknown whether they extend to estimations of liver volumes for population "outliers," such as children with overweight or obesity, who today represent one‐third of the pediatric population. Using computerized tomography or magnetic resonance imaging, this study measured liver volumes in 99 children (2-21 years) with normal weight, overweight, or obesity and compared organ measurements with estimates calculated using an established liver volume equation. A previously developed equation relating BSA to liver volume adequately estimates liver volumes in children, regardless of weight status.